1980
DOI: 10.1152/ajpgi.1980.238.3.g233
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic evidence for hepatic lobular concentration gradient of bile acid derivative

Abstract: Using an iodinated bile-acid analog with hepatic uptake and transport characteristics similar to conventional bile acids, the hepatic lobular gradient concept of Goresky was studied utilizing autoradiography. 125I-labeled cholylglycylhistamine (125I-CGH) was infused into the portal veins of male Sprague-Dawley rats and the livers were fixed for light microscopic autoradiography at 1 and 5 min after infusion. In two animals, sequential samples of bile were collected to assess the transport characteristics of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 0 publications
2
41
0
Order By: Relevance
“…A portal-to-central lobular concentration gradient for the uptake of plasma-derived substances by liver has been demonstrated previously, specifically for galactose (33)(34)(35) and the modified bile salt cholylglycylhistamine (36). However, when looked for, no such concentration gradient has been found to exist for the uptake of any plasma-derived protein thus far studied, including insulin (37), IgA (38), and apoprotein B (39).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A portal-to-central lobular concentration gradient for the uptake of plasma-derived substances by liver has been demonstrated previously, specifically for galactose (33)(34)(35) and the modified bile salt cholylglycylhistamine (36). However, when looked for, no such concentration gradient has been found to exist for the uptake of any plasma-derived protein thus far studied, including insulin (37), IgA (38), and apoprotein B (39).…”
Section: Discussionmentioning
confidence: 78%
“…Zonal differences in lobules have been well documented morphologically (40,41) and also functionally (30,(42)(43)(44). Several theories have been suggested to explain these intralobular differences, including relative differences in blood oxygen level (45), hepatocyte maturity (42,46), blood flow patterns (47), and hepatocyte receptor number or affinity for plasma-derived substances, or both (33,36). A recent study using quantitative morphology has shown that the zone 1 (periportal) sinusoidal surface-to-volume ratio is greater than that of zone 3 (pericentral) sinusoids (48), thereby favoring a greater probability of interaction in zone 1 between circulating compounds and the fenestrae of the sinusoids.…”
Section: Discussionmentioning
confidence: 99%
“…17 Bile acid uptake in the adult is highest in periportal hepatocytes. [49][50][51] However, in early postnatal life, bile acid uptake by the liver is much reduced because of immaturity or absence of transporter proteins and other elements involved, 51 and no lobular gradient for bile acid uptake is observed. 22 Thus, it is unlikely that silencing of C7ā£H mRNA expression is regulated solely by bile acids in early life.…”
Section: Discussionmentioning
confidence: 99%
“…Although in principle all hepatocytes have equal uptake capacity for bile acids (19,55), the microanatomy of the liver lobule results in a lobular concentration gradient during blood flow through the liver ( 15,16,55). We have suggested that high bile acid concentrations are responsible for major downregulation of bile acid synthesis specifically in the portal area, whereas the route is hardly affected in the pericentral zone (11,12,56).…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids are taken up efficiently by the periportal hepatocytes (15)(16)(17)(18)(19), thereby creating decreasing concentration gradients along the sinusoids (20). Consequently, periportal hepatocytes are exposed to a sixfold higher concentration of bile acids, as compared with pericentral cells ( 15,16). In line with this, a concentration-dependent and direct downregulation of bile acid synthesis, at the level of cholesterol 7a-hydroxylase, was found in vitro when cultured pig (21) and rat (22,23) hepatocytes were incubated with bile acids.…”
Section: Introductionmentioning
confidence: 99%